Pengaruh Media Pembelajaran E-Book Cerita Rakyat terhadap Kemampuan Membaca Siswa Kelas IV SDN 255 Paranglohe Kecamatan Herlang Kabupaten Bulukumba - Fajar Syamsi; Sitti Aida Azis; Maria Ulviani (Journal on Education, 2024)
The main problem in this research is that there is an influence of folklore E-book learning media on the reading ability of class IV students at SDN 255 Paranglohe, Herlang District, Bulukumba Regency. This research aims to describe the influence of folklore e-book learning media on the reading ability of class IV students at SDN 255 Paranglohe, Herlang District, Bulukumba Regency. This type of research is quantitative research that uses experimental research (pre-experimental design) with a one-group pretest-posttest design. The population in this study were all fourth grade students at SDN Paranglohe, Herlang District, Bulukumba Regency with a sample size of 22 students. The research instruments used to collect data were description tests (pretest-posttest) and observation sheets.The data analysis technique used in this research uses descriptive statistical analysis and inferential statistical analysis with the t test. The results of the research prove that there is an influence of folklore E-Book learning media on the reading ability of class IV students at SDN 255 Paranglohe, Herlang District, Bulukumba Regency.